2011
DOI: 10.5897/ajb11.3140
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Cadmium from Aqueous Solutions Using A local Fungus Aspergillus cristatus (Glaucus Group)

Abstract: Cadmium (Cd) (II) resistant strain of a marine fungus, named

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…The literature reports several studies on the interaction of heavy metals with bacterial surfaces, but just few works consider these interactions at a molecular level. Even more, the presence of a carbon source caused strain-dependent effects on Ni and V removal from the spent catalyst, as previously reported for metal uptake assays with Pseudomonas aeruginosa (Sar et al, 1998) and Aspergillus cristatus (Hassan & El-Kassas, 2012). These observed differences may be possibly related to: 1) cell wall properties, as the presence of specific anionic polymers (Öztürk, 2007), whose metal interaction capability may be altered by the presence or absence of glucose, or 2) distinctive metabolic glucose-dependent and independent, signaling pathways that may confer each strain with diverse resistance mechanisms and metal uptake patterns.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The literature reports several studies on the interaction of heavy metals with bacterial surfaces, but just few works consider these interactions at a molecular level. Even more, the presence of a carbon source caused strain-dependent effects on Ni and V removal from the spent catalyst, as previously reported for metal uptake assays with Pseudomonas aeruginosa (Sar et al, 1998) and Aspergillus cristatus (Hassan & El-Kassas, 2012). These observed differences may be possibly related to: 1) cell wall properties, as the presence of specific anionic polymers (Öztürk, 2007), whose metal interaction capability may be altered by the presence or absence of glucose, or 2) distinctive metabolic glucose-dependent and independent, signaling pathways that may confer each strain with diverse resistance mechanisms and metal uptake patterns.…”
Section: Discussionsupporting
confidence: 70%
“…nose was used as the carbon source in the medium (Krátký, Biely & Bauer, 1975). Besides, Hassan & El-Kassas (2012) studied medium compositions for Cd uptake by marine Aspergillus cristatus and showed that the main factors having negative effects on metal uptake was glucose. Thus, the results show that adaptability and metal removal capabilities differ between the strains MNSHI-9K-1, MV-9K-2, and MV-AH-1, and that each strain possesses specific abilities that may have been differentially developed due to previous adaptations attained in-situ, as they were isolated from high metal content mining sites (Gómez-Ramírez et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sorption of metals by algae generally depends on ionic charge of the metal ion, algal species and chemical composition of the metal ions in solution. They have different bioactive substances such as polyphenols, polysaccharides, lipids, proteins, vitamins, and carotenoids which have amine and several negative charge active groups, for example, carboxyl, phosphate and hydroxyl that create strong links between them and hazardous metals [14,15]. The experimental results were described using Freundlich and Langmuir adsorption models [16].…”
Section: Adsorption Of Cr(iii) Ions On the Surface Of Algae Cellsmentioning
confidence: 99%
“…With increase in environmental consciousness and strict government policies, it is imperative to search for new eco-friendly techniques to clean up contaminated water using low cost biosorbents. The rush to discover new biosorbents for removal of heavy metals has led scientists to investigate many adsorbents of biological origin like soil [15], tamarind fruit shell [16], olive stones [17], chitosan [18], hard wood bark [19], bacteria [20], algae [21], fungi [22], yeast [23], keratin [2], seaweed [24] etc Biomasses used for biosorption may be living or dead. Dead biomass or sorbents derived from them are much easier to use due to their less complex nature.…”
Section: Biosorbentsmentioning
confidence: 99%